Linking education and hospital data in England: linkage process and quality - Nicolás Libuy; Katie Harron; Ruth Gilbert; Richard Caulton; Ellen Cameron; Ruth Blackburn (International Journal of Population Data Science, 2021)
Introduction Linkage of administrative data for universal state education and National Health Service (NHS) hospital care would enable research into the inter-relationships between education and health for all children in England.